Evaluat ion and Adopt ion Scope of Rotary Power Weeder for Weed Management in Vegetable Crops - Chandel, N. S.; Tripathi, H.; Tewari, V. K. (International Journal of Bio-resource and Stress Management, 2015)
In this study, a commercial self-propelled rotary power weeder was evaluated in wide space line sown three vegetable crops i.e. tomato (Solanum lycopersicum), yard long bean (Vigna sesquipedalis) and okra (Hibiscus esculenta) crop at research field of Agricultural and Food Engineering Department IIT Kharagpur, West Bengal during 2010-13. The weeder was installed with 4 kW air cooled diesel engine with 3 forward and 2 reverse speed transmission systems. Twelve L-shape weeding blades on three flanges was attached at rearward of the self-propelled unit. Field capacity, field efficiency, weeding efficiency and plant damage was observed during the field evaluation. The observed field efficiency of self-propelled rotary weeder was 86.7, 82.4 and 87.2% and effective field capacity was 0.092, 0.080, 0.096 ha h-1 at a forward speed of 2.3, 2.0 and 2.4 km h-1 in tomato, yard long bean and okra, respectively. Effective working width of operation was 400 mm. The depth of operation was 53, 46 and 50 mm for tomato, yard long bean and okra, respectively. Weeding efficiency in tomato, yard long bean and okra was found as 96, 94 and 97%, respectively with plant damage of 1.6, 2.8 and 1.9%, respectively. Feedback from 35 respondents was conducted for adoption of rotary power weeder in vegetable crop. Analysis shows that more than 96% farmers were willing to the adoption of rotary power weeder through the custom hiring services.